Sistem Penilaian Sidang Komprehensif Tugas Akhir Skripsi dan Tesis Berbasis Yii Framework Menggunakan Business Intelligence Methodology - Nurhaeni, Tuti; Handayani, Indri; Nurcahya, Ridwan Akbar; Rifaldi, Andi (Technomedia Journal, 2020)
Evaluation of examiners is very important in giving a decision to every student. Raharja University as the organizer of higher education institutions in the field of Science and Technology continues to strive to improve the quality and quality of education and services for students or students in Information Systems innovation that is growing rapidly, one of which is PESSTA + (Thesis Assessment and Final Assignment Plus) is a system Evaluation Testing Postgraduate student trials that provide convenience in inputting the value of the Final Session of Postgraduate students. The problem this time is that examiners must be careful to input the value of the final thesis trial that is currently using the Microsoft Excel application. The purpose of this study is to design an application for inputting the value of an online thesis-based final trial. This research uses the SWOT Analysis method and Literature Study. And the Research Results in this Research is a Final Assembly Examination Assessment System which is located on the Yii Framework-based PESSTA + website which is expected to facilitate the final trial examiners at Raharja University.